EMA-CVT performance for UDDS and HWFET cycles with fuzzy logic approach - Jaffar, Abdul Hassan; Rahman, Mohammed Ataur (The Mattingley Publishing Co., Inc., 2020)
Continuously variable transmission (CVT) is moreeffective in transferring power from the engine to the wheels than gear-based transmission as it able to provide an unlimited number of gear ratios to suit different drivingenvironments. Conventional CVT system that operatesbased on hydraulic actuation mechanism experienced slow acceleration when move from stop, less torque while climbing the mountain and continuously create unpleasant noise. The hydraulic fluid viscosity falls below the optimum value when its temperature is too high due to long run and result in losses of the input power transmitting. An alternative to conventional actuation system, the electromagnetic actuation (EMA) mechanism,is discussed in this paper. The EMA forcewas controlled byvarying the supply current with a fuzzy logic controller (FLC) based on sensor input. A simulation that mimic a Toyota Wish car moves along the UDDS and HWFET driving cycles has been introduced here. The FLC was successfully producing the required current to operate the EMA for the mention driving cycles. For UDDS cycle, the system generated about 2.2-2.6 kN electromagnetic force with about 5.6-6.06 A current supply. On the other hand, for HWFET cycle with current supply of 5.75-6.05 A, the required electromagnetic force of 2.4-2.6 kN was produced. Fuzzy Logic Controller enable the system to fast response in generating the required current. For both driving cycles, the controller took about 2.1-2.2 seconds to regulate the current level from zero value to the targeted current level.